1999
DOI: 10.1108/09604529910273049
|View full text |Cite
|
Sign up to set email alerts
|

Measuring hospital service quality: a methodological study

Abstract: Quality in the service sector has been extensively researched during the last years. The publication of a sequence of measurement tools has allowed homogenizing the study of this issue. The object of the present work is to develop a methodological analysis for the use of the SERVQUAL measure scale in the Spanish public health sector. We analyse the reliability of this measure scale, its dimensionality, using comparison with other studies. Finally we consider the main criticism frequently made in the literature. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…Doctors have an obligation "to divide time equally and should not be expected to devote undue time or attention to a single patient" (Winsted, 2000). Moreover, unlike US studies (Andaleeb, 1998;Zifko-Baliga and Krampf, 1997) and Europe (Martinez Fuentes, 1999), nurse and physician competence was insignificant when Japanese outpatients assessed health Patient satisfaction…”
Section: Quality Attributesmentioning
confidence: 88%
“…Doctors have an obligation "to divide time equally and should not be expected to devote undue time or attention to a single patient" (Winsted, 2000). Moreover, unlike US studies (Andaleeb, 1998;Zifko-Baliga and Krampf, 1997) and Europe (Martinez Fuentes, 1999), nurse and physician competence was insignificant when Japanese outpatients assessed health Patient satisfaction…”
Section: Quality Attributesmentioning
confidence: 88%
“…found that five dimensions existed to measure hospital service quality (tangibles, reliability, responsiveness, assurance, and empathy). Generally, hospital service quality perception is based on patient judgment of the services provided by the hospital, for example, the relationship between the patients and nurse, doctor and staff (Martinez Fuentes, 1999). Chahal and Kumari (2010) suggest that patients base their perception of health care service quality on three dimensions: physical environment (comprising ambient condition, social factor and tangibles), interaction quality (comprising attitude and behaviour, expertise and process quality), and outcome quality (comprising waiting time, patient satisfaction and loyalty).…”
Section: Hospital Service Qualitymentioning
confidence: 99%
“…The quality of health care services has been defined as "the degree to which health services for individuals and populations increases the likelihood of desired health outcomes and is consistent with current professional knowledge" (Institute of Medicine, 2001, p. 21). Medical service quality perception is a judgment whether the service performed for a patient is the most appropriate to produce the best result that could be reasonably expected by the patient and whether those services are delivered with due attention to the doctor/patient relationship (Martinez, 1999).…”
Section: Service Quality Perceptionmentioning
confidence: 99%